Racial disparities in the optimal for induction of labor in low-risk term pregnancies: a national population-based study. (17th April 2016) - Vilchez, Gustavo; Dai, Jing; Gill, Navleen; Lagos, Moraima; Bahado-Singh, Ray; Sokol, Robert J.
Abstract: Objective : The recommendation for elective induction of labor (IOL) is to await ≥39 weeks. Studies show earlier maturity of Blacks compared to Whites. The objective was to examine the effect of the Black race on the risk of intrapartum and neonatal complications after IOL. Methods : Black women with non-indicated IOL at 37–42 weeks were selected from the CDC-Birth Cohorts 2007–2010. Congenital anomalies, hypertension/diabetes, low-birth weight, breech presentation, previous cesarean and premature rupture of membranes were excluded. Intrapartum/neonatal complications were analyzed. Logistic regression was used to calculate adjusted odds ratios, using 39 weeks as reference. Results : 311 264 black were compared with 2 451 774 deliveries of other races. For Blacks, the risks of cesarean delivery and intrapartum complications were lower at 38 weeks. Chance of vaginal delivery was greater at 38 weeks. Risks of neonatal complications was not increased at 38 compared to 39 weeks. Conclusions : Intrapartum complications were lower at 38 than at 39 weeks in Blacks with no increased risk of neonatal complications. Meconium staining and fetal distress were higher as early as at 40 weeks, perhaps due to accelerated maturation. While a 39-week goal is simple and benefits many patients, a more "personalized medicine" approach may benefit even more mothers and babies.